1997
DOI: 10.1038/sj.bjp.0701325
|View full text |Cite
|
Sign up to set email alerts
|

Carrier‐dependent and Ca2+‐dependent 5‐HT and dopamine release induced by (+)‐amphetamine, 3,4‐methylendioxy‐methamphetamine, p‐chloroamphetamine and (+)‐fenfluramine

Abstract: 1 The mechanism underlying 5-hydroxytryptamine (5-HT) and/or dopamine release induced by (+)-amphetamine ((+)-Amph), 3,4-methylendioxymethamphetamine (MDMA), p-chloroamphetamine (pCA) and (+)-fen¯uramine ((+)-Fen) was investigated in rat brain superfused synaptosomes preloaded with the 3 H neurotransmitters. 2 Their rank order of potency for [ 3 H]-5-HT-releasing activity was the same as for inhibition of 5-HT uptake (pCA5MDMA5(+)-Fen44(+)-Amph). Similarly, their rank order as [ 3 H]-dopamine releasers and dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 44 publications
10
107
3
Order By: Relevance
“…In addition to the experiments with fenfluramine further evidence that [ 3 H]N-methylspiperone was insensitive to manipulation of 5-HT levels was provided by the experiments with p-choroamphetamine. Although this compound releases 5-HT with a potency which is about twice that of fenfluramine (Crespi et al 1997), in the present study it did not affect the in vivo [ 3 H]N-methylspiperone binding.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition to the experiments with fenfluramine further evidence that [ 3 H]N-methylspiperone was insensitive to manipulation of 5-HT levels was provided by the experiments with p-choroamphetamine. Although this compound releases 5-HT with a potency which is about twice that of fenfluramine (Crespi et al 1997), in the present study it did not affect the in vivo [ 3 H]N-methylspiperone binding.…”
Section: Discussioncontrasting
confidence: 80%
“…Under in vitro conditions, the release of 5-HT is increased from brain slices, synaptosomes and cultured neurons following exposure to MDMA (Nichols et al, 1982;Johnson et al, 1986;Berger et al, 1997;Crespi et al, 1997;Azmitia et al, 1990;Sprouse et al, 1989). The MDMA-induced release of 5-HT in vitro is suppressed in the presence of drugs that inhibit the activity of the 5-HT transporter indicating that the increase in release of 5-HT likely occurs through the 5-HT transporter (Hekmatpanah and Peroutka, 1990;Gu and Azmitia, 1993;Koch and Galloway, 1993).…”
Section: Serotonergic Neuronsmentioning
confidence: 99%
“…Striatum-Under in vitro conditions MDMA has been shown to promote the release of DA from superfused brain slices, as well as prevent the reuptake of DA into brain synaptosomes (Johnson et al, 1986;Schmidt et al, 1987;Johnson et al, 1991;Steele et al, 1987). Moreover, Crespi et al (1997) demonstrated that the MDMA-induced release of DA from striatal synaptosomes is carrier-mediated and calcium dependent. Yamamoto and Spanos (1988) using in vivo voltammetry were among the first to demonstrate that MDMA at behaviorally relevant doses (i.e., 5-10 mg/kg) increases the release of striatal DA in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Although PCA also causes an acute release of dopamine (DA) (Crespi et al 1997;Henderson et al 1993;Johnson et al 1990;Ögren 1985b;Sharp et al 1986) as well noradrenaline (NA) (Ögren 1982; Ögren 1985a) in the rat brain, its behavioral effects are mediated primarily via serotonergic mechanisms (Adell et al 1989;Geyer 1996;Hutson and Curzon 1989;Trulson and Jacobs 1976). In support of this, the one-way active avoidance deficit by PCA was completely blocked when the rats were pretreated with 5-HT reuptake inhibitors zimeldine and fluoxetine but not by the NA uptake inhibitor desipramine (Ögren 1982).…”
Section: Abstract : Passive Avoidance; 5-ht Receptors; 8-oh-dpat; P-mentioning
confidence: 99%